2018
DOI: 10.1002/jcb.26547
|View full text |Cite
|
Sign up to set email alerts
|

Profiling and characterization of microRNAs responding to sodium butyrate treatment in A549 cells

Abstract: Butyrate inhibits growth of lung cancer. However, the molecular mechanism is still unclear. Here we profiled miRNAs that responded to sodium butyrate(NaB) stimulation in A549 cells, a non-small cell lung cancer cell line, using microarray. We found 33 up-regulated microRNAs and 22 down-regulated microRNAs (log2 ≥1.5 folds, P-value <0.05). The expression of miR-3935, miR-574-3p, and miR-494-3p was confirmed by realtime qPCR. Then,we explored their potential targets of miR-3935 and miR-494-3p using long noncodin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…Several in vivo and in vitro studies have reported that SCFAs, mainly butyrate, exert anticancer effects, such as suppressing cell growth, migration and invasion, on colon cancer (3,4). Recently, sodium butyrate treatment was shown to upregulate miR-3935 expression, which prohibited the proliferation and migration of A549 cells (5). However, despite studies on the roles of SCFAs in the colon, the anticancer effects of SCFAs, especially propionate, on lung cancer are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Several in vivo and in vitro studies have reported that SCFAs, mainly butyrate, exert anticancer effects, such as suppressing cell growth, migration and invasion, on colon cancer (3,4). Recently, sodium butyrate treatment was shown to upregulate miR-3935 expression, which prohibited the proliferation and migration of A549 cells (5). However, despite studies on the roles of SCFAs in the colon, the anticancer effects of SCFAs, especially propionate, on lung cancer are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, circulating levels of miR-29a have also been proposed as a biomarker for cancer progression in colorectal cancer [61]. Unfortunately little is known about miR-3935, although it has been found to be down-regulated in some neurodegenerative disorders [62], and up-regulated expression reduced proliferation and migration in A549 cells [23] .…”
Section: Discussionmentioning
confidence: 99%
“…Thus butyrate can exert an anti-cancer effect through increasing p21 via decreasing miR106B. Xiao et al (2018) studied miRs altered by butyrate in non-small cell lung cancer cell line A549 and found 33 miRs upregulated and 22 miRs down-regulated [164]. Among them, miR-3935 and miR-574-3p were most upregulated.…”
Section: Effects Of Butyrate On Micrornasmentioning
confidence: 99%